The Role Of Advertising In Public Life And The Concept Of Advertising Text - Nigora Makhmudova (Procedia of Social Sciences and Humanities, 2022)
The article discusses the role of advertising in public life and the concept of advertising text. Currently, there are different approaches to clarifying the term "advertising", on the one hand, such approaches testify to the complexity of the phenomenon, on the other hand, there are different views and opinionson its structure and nature of formation.